(untitled) (AFRICAN JOURNAL OF APPLIED RESEARCH, 2022)
The economic and social crisis in Nigeria cannot be adequately understood outside the organisation of the political economy as a dependent capitalist one. Political independence did not lead to economic liberation from imperialism as the structural and institutional foundations of imperialism were strengthened at independence and over the post-independence period. The crisis is aggravated by the continuous haemorrhage of resources from the country to the metropolitan world, lack of perspective macro-economic planning, non-diversification of the economy, and the use of the state and its organs and agencies by the ruling political elite to plunder the resources of the state. All efforts towards resolving the crisis have been a disastrous failure because most of the blueprints are formulated by the metropolitan states and their agencies with the ultimate aim to keep the state in unequal relations with the metropolitan states. Internally formulated policy instruments and economic measures have had little or no impact because they have mostly been wrongheaded. It is our argument in this paper that, the choice before the ruling elite is between the minimum programme of reforms to expand production and meet the basic needs of the people or the maximum programme of popular democratic revolutionary change of the existing political and social order.